Architected squirt-flow materials for energy dissipation. (December 2017) - Cohen, Tal; Kurzeja, Patrick; Bertoldi, Katia
Abstract: In the present study we explore material architectures that lead to enhanced dissipation properties by taking advantage of squirt-flow - a local flow mechanism triggered by heterogeneities at the pore level. While squirt-flow is a known dominant source of dissipation and seismic attenuation in fluid saturated geological materials, we study its untapped potential to be incorporated in highly deformable elastic materials with embedded fluid-filled cavities for future engineering applications. An analytical investigation, that isolates the squirt-flow mechanism from other potential dissipation mechanisms and considers an idealized setting, predicts high theoretical levels of dissipation achievable by squirt-flow and establishes a set of guidelines for optimal dissipation design. Particular architectures are then investigated via numerical simulations showing that a careful design of the internal voids can lead to an increase of dissipation levels by an order of magnitude, compared with equivalent homogeneous void distributions. Therefore, we suggest squirt-flow as a promising mechanism to be incorporated in future architected materials to effectively and reversibly dissipate energy.